PENINGKATAN PEMAHAMAN KONSEPTUAL SISWA MELALUI PEMBELAJARAN MATERIAL MANIPULATIF DALAM MATERI BILANGAN BULAT DI SMP - Bimantara, Abdul Rauf; Sugiatno, Sugiatno; Munaldus, Munaldus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to explain the improvement of conceptual understanding of students through the learning of manipulative material in the matter of integers at SMP Negeri 8 Pontianak academic year 2017/2018. The research method used is Single Subject Research (SSR) method with A-B-A-B design. The subjects of this research are students of class VII E Junior High School 8 Pontianak, amounting to 5 students. Data collection techniques used were measurement techniques. The data collection tools used test. The results of data analysis from this research indicate that there is an improvement of conceptual understanding of students through the learning of manipulative material in the material of addition operation and reduction of integer with each phase a conceptual understanding test of 1 session was obtained by baseline phase 1 with an average percentage of 24.54%, treatment phase 1 with an average percentage of 69.09%, baseline phase 2 with a percentage of 72.72% and phase treatment 2 with a percentage of 90%. Keywords:  Conceptual Understanding, Manipulative Material